Health Film Promotion Media And Motivation On Community Knowledge In Preventing Dengue Fever - M. Indra Tarigan; Muhammad Badiran; Linda Hernike Napitupulu (Pena Cendekia Insani, 2020)
Introduction: Efforts to control dengue fever can be accomplishedby promoting health awareness among those at risk of contracting thedisease. Numerous factors, such as the health promotion methods andmedia used, will have an effect on health promotion. Method: Theresearch method used is quasi-experimental with a factorial 2x2design. The study sampled 66 individuals. The analysis in this studyemployed a two-lane variance (ANAVA) analysis with a confidencelevel of 95 percent Result : The findings of this study indicate thatcommunity knowledge about DHF prevention with companiondiscussion is greater than community knowledge about DHFprevention without companion discussion. The knowledge of highlymotivated communities is greater than the knowledge of lowmotivated individuals. There is a relationship between extensionstrategies and motivation for a healthy lifestyle in terms ofinfluencing public knowledge.Conlusion The Finale There is arelationship between extension strategies and motivation for ahealthy lifestyle in terms of influencing public knowledge. It issuggested to the puskesmas officer that he conduct extension effortson DHF disease prevention by using film media in conjunction withdiscussion to increase public awareness of DHF disease prevention